The Development of Modern Islamic Law In The Lembaga Bahtsul Masa'il Nahdlatul Ulama - Zulfan Efendi; Asrizal Saiin; Muhammad April; Muh. Rizki (Journal of Nahdlatul Ulama Studies, 2022)
Nahdlatul Ulama is a major Islamic organization in Indonesia. In deciding a law, Nahdlatul Ulama has a forum called the Lembaga Bahtsul Masa'il (LBM). This paper examines the developments in the determination of Islamic law by the Lembaga Bahtsul Masa'il. The method used is a qualitative research method with a normative approach. While the data sources used are secondary data sources with data processing and analysis in five stages, namely editing, grouping, verification, analysis, and drawing conclusions. The results obtained are that the Lembaga Bahtsul Masa'il in establishing a law is always developing. As a forum for determining NU's Islamic law, the Lembaga Bahtsul Masa'il not only always discusses fiqh issues, but also discusses other issues outside of fiqh, namely modern issues regarding state policies and legislation that are in direct contact with the interests and welfare of the community, such as the issue of protection of religious communities through laws; Implementation of Religious Education in Schools (Improved PP No. 55 of 2007); Organizing cheap and quality regional head elections; Natural Resources (SDA) for the welfare of the people; Shortening the waiting period for prospective pilgrims and managing Hajj finances; Protection of Indonesian Migrant Workers and Marriage Registration for Indonesian Muslim Migrant Workers abroad; and Improving the management of BPJS Kesehatan.